Analisis Hasil Terjemahan Sulih Suara Istilah Budaya Film Storybook: The Enchanted Attic - UMMATIN, KHOIRU (Jurnal Penerjemahan, 2018)
This study aims to describe the dubbing translation techniques employed in the translation of cultural terms in the movie “Storybook: The Enchanted Attic” aired on JTV. This research is conducted by applying the theory about dubbing translation techniques as proposed by Garcarz. This research utilizes the close watching and recording techniques to collect the data, which are then analyzed descriptively based on the research problem and the theory framework. From the analysis of the film, it is revealed that the most commonly used dubbing translation technique is the closest synonym technique. This technique is widely used in cultural terms related to swearing. The translator endeavours to maintain the context of the story in the source languange by finding the closest synonym in the target language in order to retain the target culture. Keywords: dubbing, translation technique, cultural term, film